A comparison of morbidity patterns in public and private primary care clinics in Malaysia - Mimi, O.; Tong, S.F.; Nordin, S.; Teng, C.L.; Khoo, E.M.; Kareem, A.R.A.; Zailinawati, A.H.; Lee, V.K.M.; Chen, W.S.; Shihabudin, W.M.; Noridah, M.S.; Fauziah, Z.E. (Academy of Family Physicians of Malaysia, 2011)
Objectives: To compare the morbidity patterns in public and private primary care clinics; determine patients' reasons for encounter (RFE) and diagnoses using the ICPC-2, and compare ten commonest diagnoses and RFEs. Methods: A cross-sectional study on randomly selected clinics was conducted nationwide. Doctors completed the Patient Encounter Record (PER) for systematically selected encounters for a week. Results: Response rate was 82.0 (public clinic) and 33 (private clinic) with 4262 encounters and 7280 RFE. Overall, the three commonest disease categories encountered were respiratory (37.2), general and unspecified (29.5), and cardiovascular diseases (22.2). Public and private clinics handled 27 versus 50 acute cases and 20.0 versus 3.1 chronic cases i.e. 33.7 and 5.6 chronic diseases/100 RFE respectively. Conclusion: Doctors in public clinics saw more chronic and complex diseases as well as pregnancy related complaints and follow-up cases while in private clinics more acute and minor illnesses were seen. Health services should be integrated and support given to co-manage chronic diseases in both sectors. Â© Academy of Family Physicians of Malaysia.